Wrap N' Roll: A feasibility study of a triangular spring roll dessert - Cruz, Heindrix G.; Eda, Althea Marie B.; Marquez, Ysabelle G.; Mascariñas, Krystal Bell S.; Mercado, Dianne Nicole; Mogado, Kyle Samantha, Repulledo, Danica Rose O.; Roque, Princess Jem P. 4 0 16; 5
EXECUTIVE SUMMARY: This executive summary presents the overview of the feasibility study. It provides a Description on the proposed business. Additionally, it summarizes the different aspects of business, such as management, marketing, technical, financial, and socio-economic aspects, which are vital in administering the proposal. BUSINES DESCRIPTION: The Philippines has a vibrant culture, and a diverse culinary landscape converges to create a unique phenomenon deeply cherished by its inhabitants: meryenda . Loosely translating to light snack in English and came from the Spanish word merienda or afternoon snack, this has become an integral part of Filipino like, especially youngsters. Its popularity can be attributed to a rich tapestry of cultural, social, and practical factors that make it more than just a simple meal break; it's a reflection of the heart and soul of Filipino life. Filipinos are used to knowing such sweet meryenda like Turon, Banana Cue, Kamote Cue, Maruya, and other rice cakes that are quite popular and can be bought always in the streets or homes of their neighborhood. The lack of options and consuming the same sweet food can be a dilemma for people as they get to have enough of it and look for other products. Within the Walled City, only the above-mentioned products are available that are good for the masses taste. Moreover, the place is somehow a good location to put up a business as the workers, students, locals, and even foreigners are going in and out of the location. In the competitive world of the food industry, innovation, and uniqueness are key factors that can set a business apart. Hence, the proponents came up with Wrap N' Roll an exciting introduction of sweet-filled spring rolls inside the wall of Intramuros. The heart of this business lies in its unique sweet fillings. Instead of the traditional meryenda we know as Turon which is made of banana, jackfruit and sugar, we offer an array of delightful options like Choco Mallows, Ube Cheese, Peach Mango, and Buko Pie which has a drizzle of either chocolate or caramel syrup based to the liking of the customer. This enterprise is not just about selling snack food; it's about creating a memorable culinary experience that caters to the diverse taste of the community in Intramuros. Wrap N' Roll venture is a partnership business located inside the vicinity of Intramuros, specifically on Walls Muralla Street lined with the famous Spicy Chicken Stall and in front of Mapua University. It focuses on giving the Intramuros Community the taste of a cultural fusion sweet snack in the form of like Turon or Shanghai we all know which is wrapped food in a triangle shape that is perfect for students, employees, locals and tourists. Hence, the business name was developed since we will incorporate other fillings we discovered and formulated in a lumpia wrapper and roll it. The business goal is to ensure that our customers always get an affordable at best, fresh, and delicious product.
Feasibility Study: (BSBA major in Human Resouce Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2